PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, KOMISARIS INDEPENDEN, KOMITE AUDIT, PERGANTIAN AUDITOR, DAN UKURAN KAP TERHADAP INTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR PERIODE TAHUN 2012-2016 - Ngesti Utami Putri, 11.05.52.0080; Kartika, Andi (Students Journal of Accounting and Banking, 2018)
Every company needs financial information obtained from financial statements. The financial information presented should be in accordance with the real circumstances and are relevant so as to provide benefits to the recipient of the information. Financial information contains the financial data presented in description of the companys financial condition, the information contained in the financial statements. The population in this study is a manufacturing company listed in Indonesia Stock Exchange period 2012-2016. The sample in this research is 22 companies. The analysis tool used is Multiple Linear Regression. The results of this study indicate the variable of institutional ownership have a significant positive effect on the integrity of financial statements. Managerial ownership has a significant positive effect on the integrity of financial statements. Independent commissioners have no effect on the integrity of financial statements. Audit Committee has a significant effect on the integrity of financial statements with negative coefficient direction. Substitution of auditors has a significant positive effect on the integrity of financial statements. The size of the KAP has a significant effect on the integrity of the financial statements with the direction of the negative coefficient.Keywords: Institutional Ownership, Managerial Ownership, Independent Commissioner, Audit Committee, Audit Substitution, and Size KAP and Integrity Financial Statemen